Influence Contextual Factor on the Indonesian Journalist’s Job Competency: Proactive Behavior as Mediator - Nuraeni, Reni; Tan, Cheng-Ling; Azwan Azmawati, Azman (International Journal of Engineering and Technology, 2018)
This study focuses on examining the influence of contextual factor on the Indonesian Journalist’s Job Competency. The literature review indicated journalist practices of a contextual factor influence Journalist’s Job Competency. The synthesis of the literature reveals that the proactive behavior can be used as a mediator to link the relationships of a contextual factor, and Journalist’s Job Competency. So far, no attempt has been made to integrate the journalist factor of contextual with adaptive journalist proactive behavior. This study aims to trigger the better understanding of the factors that can help to improve the journalist job competency. This proposed conceptual frameworks would be tested empirically via survey questionnaires.
Keywords: Journalist; Job Competency; Proactive Behavior; Contextual Factors